Collapse safety margin-oriented seismic retrofit strategy for corroded reinforced concrete frames using fibre reinforced plastics. Issue 8 (3rd August 2019) - He, Zheng; Ou, Xiaoying; Li, Jiangwei; Ou, Jinping
Abstract: Considering residual service life, this paper presents a collapse safety margin-oriented seismic retrofit strategy for corroded reinforced concrete (RC) frames using fibre reinforced plastics (FRP). With the assumed uniform corrosion model, corrosion-induced initial damage combined with subsequent earthquake-induced damage is identified by the multi-mode-based global damage model developed previously. The collapse-level earthquake intensity determined by incremental dynamic analyses (IDA) with the damage model and the maximum considered earthquake (MCE)-level intensity considering residual service life are combined to generate the time-variant collapse safety margin assessment of corroded RC structures. Based on this assessment, the collapse safety margin-oriented FRP seismic retrofit strategy is proposed and demonstrated on a 4-storey frame. The damage model originally developed for earthquake scenarios has also exhibited its rationality for characterising corrosion-induced initial damage and its influence on coupled damage development with subsequent earthquake excitation. Seismic retrofitting with FRP composites should consider the effects of the corrosion development stage, target collapse safety margin and residual service life. FRP retrofits can cause decreases in the MCE-level collapse probability and increases in the collapse resistance of corroded RC structures. Retrofitting carried out at different times achieves different efficiencies and different time-variant collapse safety margins within the residual service life.